"SOFT POWER": THE DARK SIDE (ON THE CASE OF GERMANY) - M. M. Lebedeva; L. R. Rustamova; M. V. Sharko (Vestnik MGIMO-Universiteta)
Despite of the fact that numerous researches on the concept of soft power were conducted by Russian as well as by foreign scholars, negative aspects of soft power, especially concerning actors that implement it, were almost disregarded. This article focuses on possible adverse consequences for such actors and illustrates them with the example of Germany that intensively forms its attractive image in the international arena. The authors affirm in particular that actors should form their comprehensive positive image rather than attractiveness of distinct spheres and features. They should also consider side-effects of soft power and harmonize NGO's activities in implementation of this policy. The latter is becoming more relevant against the background of broader application of soft power through public diplomacy with the help of non-governmental organizations. In addition, the article emphasizes the necessity of further theoretical and empirical researches on the issue.